PROTOTYPE APLIKASI BUKU PENGHUBUNG BERBASIS MOBILE - Wahyu Tisno Atmojo; Afifah Trista Ayunda; Indras Nur Hidayat (Jurnal Komputasi, 2024)
Abstract — The Liaison Book is a media of communication between the school, especially the class teacher and parents, parents can monitor student activities at school through the liaison book. The liaison book needs to be made an application because of the many problems that exist today where these problems include frequent damage to the liaison book, students forgetting to bring the liaison book, parents not reading the liaison book or students not giving the liaison book to parents or teachers. This application prototype is made using the Waterfall method with the java programming language and Android Studio tools. The result of this research is an application that is feasible to use where 62% of respondents strongly agree that this application is used, 31% of respondents agree to use it and as many as 7% expressed doubt. From the percentage of these answers it can be seen that this application is indeed feasible to use.